Non-responsive feeding practices mediate the relationship between maternal and child obesogenic eating behaviours. (1st August 2020) - Miller, Narissa; Mallan, Kimberley M.; Byrne, Rebecca; de Jersey, Susan; Jansen, Elena; Daniels, Lynne A.
Abstract: Both genetic and environmental influences underpin complex multidimensional associations between maternal and child eating behaviours, maternal feeding practices and child obesity risk. The aim of the present study was to explore cross-sectional relationships between maternal and child eating behaviours, and to examine whether maternal feeding practices mediate these relationships. Data were available from 478 Australian mothers ( M  = 38.8 years, SD  = 5.6) of a 5–10 year old child ( M  = 7.0 years, SD  = 1.1; 48.2% male). Mothers completed an online survey that included validated measures of maternal eating behaviours, maternal feeding practices and child eating behaviours. Maternal emotional overeating and food responsiveness, were each positively associated with the parallel child eating behaviour ( r  = 0.29 and r  = 0.21, p s < .001, respectively). Mediation analyses showed that both the relationship between maternal and child emotional overeating and between maternal and child food responsiveness, were partially mediated by use of food as a reward and overt restriction (total indirect effect: .04, 95% CI 0.02, 0.07 and 0.82, 95% CI 0.04, 0.13, respectively). Findings suggest a role for feeding practices in explaining the concordance between maternal and child eating behaviours. Moreover, the results highlight the need for interventions that support parents to recognise these eating behaviours in themselves and their children and understand how these may potentially influence the feeding practices they use. Future longitudinal research that confirms the cross-sectional relationships between maternal and child eating behaviours and feeding practices reported here will strengthen the evidence to support the importance of feeding practices in the development of dietary intake patterns and obesity risk.